2023
DOI: 10.1186/s12912-023-01198-9
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between job stress and patient safety culture among nurses: a systematic review

Abstract: Background Work stress is one of the leading causes of physical and mental problems among nurses and can affect patient safety. Nurses experiencing stress are more prone to make errors, which has consequences for the safety culture. This study aimed to describe the findings of studies that examined the relationship between job stress and patient safety culture among nurses. Methods A systematic review of published English-language articles from 201… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…This result was consistent with a study in the United States that found a correlation between patient safety dimensions and patient safety grade. 36 In private healthcare facilities, only two dimensions (Hospital Management Support for Patient Safety, Staffing, and Work Pace) significantly correlated with patient safety grades. This study found a significant difference in the perception of patient safety culture across the three healthcare facility levels, and that facility type predicted the overall perception of patient safety.…”
Section: Discussionmentioning
confidence: 96%
“…This result was consistent with a study in the United States that found a correlation between patient safety dimensions and patient safety grade. 36 In private healthcare facilities, only two dimensions (Hospital Management Support for Patient Safety, Staffing, and Work Pace) significantly correlated with patient safety grades. This study found a significant difference in the perception of patient safety culture across the three healthcare facility levels, and that facility type predicted the overall perception of patient safety.…”
Section: Discussionmentioning
confidence: 96%
“…The main manifestations include strict adherence to nursing work regulations, correct implementation of nursing operating procedures, effective execution of medical orders, scientific and objective recording of nursing documents and safety management of the hospital environment. In adhering to the principle of patient safety, identifying risks and hazards through nursing evaluation, establishing nursing plans, effective patrols, arranging reexaminations, and providing assistance is an important indicator of nursing quality and an important link in preventing nurse patient disputes (Zaitoun et al, 2023) Whether patient safety goals are implemented in place, or the incidence of adverse events are soundly controlled, are closed associated with the safety behaviour of nurses. However, in practical work, there is a significant gap between patient safety goals and nurse safety behaviour (Zhang, Feng, et al, 2022).…”
Section: Importance Of Nurses' Safety Behaviourmentioning
confidence: 99%
“…A supportive work environment plays a crucial role in managing work‐related stress and shaping conflict management style among emergency care nurses (Zabin et al., 2023). A supportive work environment in EDs provides nurses with the necessary resources, tools, and systems to effectively cope with the demanding nature of their work.…”
Section: Introductionmentioning
confidence: 99%